2018
DOI: 10.20485/jsaeijae.9.3_124
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis for Investigating the Effects of Muscle Activation on Head-neck Injury Risks of Drivers Rear-ended by a Car after an Autonomous Emergency Braking

Abstract: Avoidance of frontal collisions by autonomous emergency braking (AEB) in sudden traffic jams has the potential to cause rear-end collisions by the following cars. In this study, finite element analyses using a human body model were performed to investigate how the muscle activations of drivers rear-ended by the following car could affect head-neck injury risks. Three muscle conditions of sleeping, relaxed, and braced drivers were assumed using a developed muscle controller. The simulation results suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Some previous studies investigated the influences of the muscle foreces on head neck injuries, but they generally adopted assumed or PID-based muscle activations [11,13,15]. To our knowledge, no study reported the effects of realistic human neural reflex on head-neck impact responses during impact environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies investigated the influences of the muscle foreces on head neck injuries, but they generally adopted assumed or PID-based muscle activations [11,13,15]. To our knowledge, no study reported the effects of realistic human neural reflex on head-neck impact responses during impact environments.…”
Section: Discussionmentioning
confidence: 99%
“…Taking the FE models as examples, the SAFER A-HBM developed in the previous studies modeled the human's reflexes mechanism for controlling cervical spine muscle activation [5][6][7][8][9][10][11][12]. The THUMS Version 5 included Proportion-Integral-Derivative (PID) based active muscle controllers for all body regions [13]. An angle-based and length-based active muscle controller was implemented in the ViVA OpenHBM [12].…”
Section: Introductionmentioning
confidence: 99%